2002
DOI: 10.1074/jbc.m208374200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Trypanosoma brucei and Leishmania major Genes Encoding the GlcNAc-Phosphatidylinositol De-N-acetylase of Glycosylphosphatidylinositol Biosynthesis That Is Essential to the African Sleeping Sickness Parasite

Abstract: The second step of glycosylphosphatidylinositol anchor biosynthesis in all eukaryotes is the conversion of D-GlcNAc␣1-6-D-myo-inositol-1-HPO 4 -sn-1,2-diacylglycerol (GlcNAc-PI) to D-GlcN␣1-6-D-myo-inositol-1-HPO 4 -sn-1,2-diacylglycerol by GlcNAc-PI de-N-acetylase. The genes encoding this activity are PIG-L and GPI12 in mammals and yeast, respectively. Fragments of putative GlcNAc-PI de-N-acetylase genes from Trypanosoma brucei and Leishmania major were identified in the respective genome project data bases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 52 publications
2
95
0
2
Order By: Relevance
“…replacement of one allele followed by introduction of tetracycline-inducible ectopic copy and then replacement of the second allele) (7,15,50). However, using the same constructs, we failed to obtain even a single allele replacement in bloodstream form T. brucei.…”
Section: The T Brucei Gdp-fucose Biosynthesis Enzymes Are Active In mentioning
confidence: 71%
See 1 more Smart Citation
“…replacement of one allele followed by introduction of tetracycline-inducible ectopic copy and then replacement of the second allele) (7,15,50). However, using the same constructs, we failed to obtain even a single allele replacement in bloodstream form T. brucei.…”
Section: The T Brucei Gdp-fucose Biosynthesis Enzymes Are Active In mentioning
confidence: 71%
“…RT-PCR performed with mRNA from day 10 cells showed that these cells were re-expressing the TbGMD ORF (data not shown). This kind of escape from tetracycline control of gene expression is a common feature of conditional null mutants of essential genes in bloodstream form T. brucei (7,15). The procyclic form mutants grew at the same rate for the first 7 days with and without tetracycline (Fig.…”
Section: Loss Of Tbgmd Expression Results In Depletion Of Gdp-fucose-tomentioning
confidence: 99%
“…The low steady-state concentrations of the cellular GDP-Man pools and the very high rates of flux through them suggests that inhibition of GDP-Man biosynthesis would have rapid and profound effects on glycoconjugate biosynthesis, and consequently on viability and/or virulence, in these organisms. Certainly, GDP-Man and Dol-P-Man biosynthesis may be assumed to be essential in bloodstream form T. brucei, where disrupting GPI anchor biosynthesis (which is dependent on Dol-P-Man made from GDP-Man) is known to be lethal for the parasite (15,26,60,74). Since Man is present in every known type of trypanosomatid glycoconjugate carbohydrate chain, with the exception of the O-linked side chains of the T. cruzi mucins, GDP-Man biosynthesis has potential as a therapeutic target against all three parasites, so long as parasite-selective inhibitors can be found.…”
Section: Cruzi) Gdp-man Is Also the Precursor Of Gdp-fuc (See Below)mentioning
confidence: 99%
“…Phosphatidylinositol glycan, class L is an enzyme that catalyzes the deacetylation of N-acetyl-D-glucosaminylphosphatidylinositol in glycosylphosphatidylinositol anchor biosynthesis. The enzymes from a variety of species have a section of sequence, AHPDDE, that carries the metal binding histidine and aspartate residues, as well as the catalytic general base aspartate (11,31).…”
Section: Figmentioning
confidence: 99%